Efektifitas Pemberian Edukasi Dengan Menggunakan Metode Penyuluhan Mengenai KB Terhadap Pengetahuan Ibu-Ibu Di Gampong Paya Baroh Bandar Dua Pidie Jaya - Ambia Nurdin; Rizka Auva Rafiqi; Bukhari Bukhari; Amiruddin Amiruddin; Zakiyuddin Zakiyuddin; Ricky Dear Fitria; Fauzi Aldina; Hendra Cipta; Muhammad Haikal (Pusat Riset dan Inovasi Nasional, 2023)
Family Planning (KB) is a government program to limit the number of children by preventing pregnancy, births that can delay pregnancy, the desired spacing of children to regulate the rate of population growth. This study used a pre-experimental design with the type of one group pretest-posttest design. The population in this study are mothers. The sampling technique used is total sampling. In the study the independent variable was the provision of counseling about family planning, while the dependent variable was the knowledge of the women of Paya Baroh village, kec. City of two, district. Pidie triumph. The type of instrument used in this research is a questionnaire. The number of samples taken was 25 respondents. It is known that most of the respondents were female as many as 25 respondents with a percentage of 100%, while most of them were aged 25-34 years as many as 10 respondents with a percentage of 40%. The level of knowledge before being given counseling was categorized as high by 6 respondents or 24%. The level of knowledge after being given counseling is categorized as high by 25 respondents or 100%. The level of family planning knowledge before and after most of the respondents increased from an average value of 2.12 to 1.00. From these results it can be concluded that there were positive results from the counseling process carried out.